Cognitive Impairment in Non-critical, Mild-to-Moderate COVID-19 Survivors - Henneghan, Ashley M.; Lewis, Kimberly A.; Gill, Eliana; Kesler, Shelli R. (Frontiers in Psychology, 2022)
Importance: Previous studies of post-acute COVID-19 syndrome have focused on critical cases with severe disease. However, most cases are mild to moderate in disease severity. Objective: We aimed to examine cognitive outcomes in cases of non-critical, mild to moderate COVID-19. Design, Setting and Participants: In this cross-sectional study, we enrolled 72 adults aged 22 to 65 years in Central Texas who had non-critical, mild to moderate COVID-19 infection between January 13, 2021 and April 20, 2021. Main Outcomes and Measures: We remotely administered cognitive-behavioral testing to determine the frequency of cognitive impairment and examine demographic, clinical, and psychosocial contributors to impairment. Results: The frequency of objective cognitive impairment was 40%. The largest number of participants (24%) showed impairment on a measure of executive functioning. Attention and processing speed was more impaired in males (OR = 1.5, 95%CI = 0.23 to 2.9). Males endorsed lower adherence to social distancing guidelines (U = 590, p = 0.01), which was in turn associated with cognitive impairment across participants (r = -0.30, p = 0.01). Younger age was correlated with impairment (r = -0.26, p = 0.03) but was also associated with racial/ethnic minority status (r = -0.31, p = 0.01) and increased psychological symptoms (p < 0.04). Greater number of COVID-19 symptoms was correlated with lower subjective cognitive function (r = -0.38, p = 0.001) as well as psychosocial function (r >0.24, p < 0.05). Moderate COVID-19 severity was associated with attention/processing speed impairment (r = 0.27, p = 0.03), increased pain (r = 0.31, p = 0.01) and higher number of COVID-19 symptoms (r = 0.32, p = 0.01). Conclusions and Relevance: Mild or moderate COVID-19 infection may be associated with cognitive impairments, especially in the domain of executive functioning. A subgroup of younger individuals who identify as a racial/ethnic minority may be more vulnerable to cognitive and psychosocial effects of COVID-19.